City of night [compact disc, unabridged] - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Dean Koontz's Frankenstein (Books on Tape, Inc.), 2005)
They are stronger, heal better, and think faster than any humans ever created-and they must be destroyed. But not even Victor Helios-once Frankenstein-can stop the engineered killers he's set loose on a reign of terror through modern-day New Orleans. Now the only hope rests in a one-time "monster" and his all-too-human partners, Detectives Carson O'Connor and Michael Maddison. Deucalion's centuries-old history began as Victor's first and failed attempt to build the perfect human-and it is fated to end in the ultimate confrontation between a damned creature and his mad creator. But first Deucalion must destroy a monstrosity not even Victor's malignant mind could have imagined-an indestructible entity that steps out of humankind's collective nightmare with one purpose: to replace us.